(untitled) (Bangladesh Journal of Zoology, 2018)
The embryonic proteomics that drift in the adult stage and responsible for performing visual activities including, biting and maintaining the vectorial life of dengue vector Aedes albopictus is not projected earlier. In a series of experiments we have indicated the concentration and extension of early proteomic cursors in the latter stages of life cycle up to the early emerging adult. We noticed about 70% gain of protein during larval developmental stages, until pupation. Newly emerged adult mosquitoes lost about 12% of protein than the pupal stage. In case of peptides, we observed 14-26 polypeptide bands during immature and early adult stages by using 12% of separating gel in ID SDS-PAGE. The bands in early larval stages up to 4th instar larvae were in the range of approximately 58 to 7 kDa, while in pupal and adult stages they were between 200 and 7 kDa. Newly emerged bands in pupal (i and ii) and adult (iii-vi) stages could be identified as stage specific peptides. The band number 10, which migrated at the same position in the PAGE with equal strength in all stages was identified as an essential peptide. Characterization of the above peptides might help in the pin pointing to possible virus transmission blocking mechanism of this vector insect. Bangladesh J. Zool. 45(2): 171-183, 2017